Construction of a model of deformation and short-time damageability for a laminate composite on the basis of the deformation criterion of microstrength - Khoroshun, L.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
A structural theory of the coupled processes of deformation and short-time damageability for laminate composites with physically nonlinear components and with the decreasing branches of deformation diagrams is constructed. The damageability is modeled by the dispersed destruction of microvolumes of a material and the formation of stochastically arranged quasispherical micropores instead of them. As a condition of short-time destruction of a microvolume of the material, the deformation criterion of strength relative to the second invariant of the deviator of microstrains is assumed. A regularity of the effect of volume components on the deformation and damageability of the laminate composite is studied.